2017
DOI: 10.3847/1538-4357/836/1/47
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against Star-forming Galaxies as the Dominant Source of Icecube Neutrinos

Abstract: The cumulative emission resulting from hadronic cosmic-ray interactions in star-forming galaxies (SFGs) has been proposed as the dominant contribution to the astrophysical neutrino flux at TeV to PeV energies reported by IceCube. The same particle interactions also inevitably create γ-ray emission that could be detectable as a component of the extragalactic γ-ray background (EGB), which is now measured with the Fermi -LAT in the energy range from 0.1 to 820 GeV. New studies of the blazar flux distribution at γ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 87 publications
10
167
0
Order By: Relevance
“…A flux of cosmogenic neutrinos as predicted by Kotera et al (2010) would only contribute subdominantly to the measured astrophysical neutrino flux. Neutrino fluxes from blazars and star-forming galaxies are predicted by e.g., Murase et al (2014) and Bechtol et al (2015), respectively. Glüsenkamp (2016) already constrains this blazar model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A flux of cosmogenic neutrinos as predicted by Kotera et al (2010) would only contribute subdominantly to the measured astrophysical neutrino flux. Neutrino fluxes from blazars and star-forming galaxies are predicted by e.g., Murase et al (2014) and Bechtol et al (2015), respectively. Glüsenkamp (2016) already constrains this blazar model.…”
Section: Discussionmentioning
confidence: 99%
“…The black crosses corresponds to experimental data and blue/red to the conventional atmospheric/astrophysical expectation weighted to the best-fit spectrum. Figure 5) with theoretical neutrino flux predictions corresponding to different source types (Kotera et al 2010;Murase et al 2014;Bechtol et al 2015;Senno et al 2016). Since Murase et al 2014 predicts a lower and upper flux bound for neutrinos originating from blazars the central line between both bounds is shown.…”
Section: Test For Anisotropies Related To the Galactic Planementioning
confidence: 99%
See 1 more Smart Citation
“…As discussed by various authors (e.g. [87][88][89]), sources which could reproduce the flux of the extragalactic diffuse PeV neutrinos detected with IceCube [90] are at risk of violating the diffuse 1-800 GeV γ-ray background seen by Fermi. Thus, since in our case the neutrino flux is well below the IceCube limits, also the related diffuse GeV γ-ray background is expected to be well below the Fermi limits.…”
Section: Acceleration Site and Possible Neutrino Emissionmentioning
confidence: 99%
“…This limit however is quite model dependent given the strong time variability of blazars. Finally a study on the diffuse extragalactic background as observed by Fermi-LAT, rules out star-burst galaxies as the major component of the neutrino astrophysical flux [16].…”
Section: The Search For Sources Of the Very-high-energy Neutrinosmentioning
confidence: 99%